2021
DOI: 10.1016/j.bbih.2021.100380
|View full text |Cite
|
Sign up to set email alerts
|

The role of lymphocytes in neonatal encephalopathy

Abstract: Neonatal encephalopathy is a syndrome characterised by abnormal neurological function often caused by a hypoxic insult during childbirth. Triggers such as hypoxia-ischaemia result in the release of cytokines and chemokines inducing the infiltration of neutrophils, natural killer cells, B cells, T cells and innate T cells into the brain. However, the role of these cells in the development of the brain injury is poorly understood. We review the mechanisms by which lymphocytes contribute to brain damage in NE. NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…The association between ferroptosis and immune infiltration is extremely complex. It has been confirmed that lymphocytes have a protective role in neonatal encephalopathies, such as decreased T cells increase inflammatory cell infiltration, primarily neutrophils, and inflammatory macrophages, which contribute to increased HI-induced brain damage, indicating that regulatory T cells in the injured brain may be an important mechanism of endogenous neuroprotection [ 50 , 51 ]. Previous studies have shown that the cytotoxicity in neonatal NK cells and low expression levels of L-selectin and CD54 lead to impaired ability to adhere to target cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between ferroptosis and immune infiltration is extremely complex. It has been confirmed that lymphocytes have a protective role in neonatal encephalopathies, such as decreased T cells increase inflammatory cell infiltration, primarily neutrophils, and inflammatory macrophages, which contribute to increased HI-induced brain damage, indicating that regulatory T cells in the injured brain may be an important mechanism of endogenous neuroprotection [ 50 , 51 ]. Previous studies have shown that the cytotoxicity in neonatal NK cells and low expression levels of L-selectin and CD54 lead to impaired ability to adhere to target cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, Zfra1-31 or 4-10, and WWOX7-21 peptides, and antibodies against Hyal-2 or pY216-Hyal-2 are known ligands for activating Z cells [ 68 ]. Inflammatory NK cells kill cancer cells and cause damage to neurons [ 75 , 76 , 77 , 78 ]. In contrast, activated Z cells protect neurons from being damaged [ 71 ].…”
Section: Zfra4-10 Activates Hyal-2/wwox/smad4 Signaling Pathway For R...mentioning
confidence: 99%